Faktor-Faktor yang Berhubungan Dengan Penerimaan KIE Kesehatan Reproduksi dan Seksual Bagi Calon Pengantin - Darma yanti; Supiyah Supiyah; Rosa Mesalina (Jurnal Sehat Mandiri, 2022)
Knowledge and attitudes of bride and groom are still lack toward reproductive health. Research in Pemalang (2019), 70% of respondents have low knowledge and 30% of respondents with attitudes do not support reproductive health. This is influenced by acceptance of an object. The implementation of pre marital counseling is a solution to this problem with the aim bridge increase their knowledge and attitudes about sexual reproductive health. The purpose of this study was to determine the relationship between sociodemography, knowledge, attitudes and income with the acceptance of pre marital counseling. The research with a cross sectional design. 87 respondents taken by cluster sampling. Data analysis was univariate, bivariate using Chi Square test and logistic regression for multivariate analysis. Results showed 85.1% of respondents were of the right age, 50.6% were male, 54% had secondary education and 88.5% were employed. Most of the material in pre marital counseling has not been received optimally by the respondents. There is a significant relationship between knowledge (0.000) and attitude (0.007) with acceptance of IEC material. The result of multivariate analysis of knowledge is the main predictor for it (p=0.001, Exp 0.187) with a correlation strength of 30.8%. Conclusion is recommended that good knowledge about sexual reproductive health supports the acceptance of pre marital counseling. It means a supporting structure for the implementation program is needed by taking the capabilities facilitator, methods and media used.